PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS KEBUDAYAAN LOKAL DI TK SUNKIDS PALEMBANG - Marina; Tuti Firdayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
During the learning process, teachers are still focused on reading, writing and arithmetic learning which is still focused on the teacher so that the effectiveness of teachers in providing learning materials is not very pleasing. There is still a lack of learning media or learning modules based on local culture in schools. The method used in this study is the research and development method. Analysis, Design, Development, Implementation, Evaluation. The results of the product trial conducted at Sunkids Kindergarten Palembang produced a score of 68% indicating EFFECTIVE results, media validation produced a score of 93.7% indicating VERY VALID results and material validation produced a score of 155.0% indicating VERY VALID results